The Life and Death of a Treaty Bermuda 2 - Stevens, Handley (Springer International Publishing, 2018)
This book offers an exceptionally well informed and well documented study of the processes by which a Treaty is not only created, but managed and adapted as a living organism, responding to changing political and economic circumstances throughout its life. Bermuda 2, which governed air services between the UK and the USA from 1977 till 2008, had to accommodate rapid but volatile market growth, conflicting policies for a more open market, and a market structure which evolved from national champions to multinational alliances. With stakes high enough for Presidents and Prime Ministers to intervene at key moments, the dramatic narrative (Part I) is helpfully cross-referenced to a fully annotated Treaty text (Part II) as well as a unique collection of supplementary documents (Part III). These three elements offer students of international law and international relations, as well as to-day's post-BREXIT practitioners, a comprehensive guide to the wide range of legal instruments and negotiating strategies that may be used to govern and regulate a major industry within the framework of a Treaty relationship.